Dominique Fourcade: Recalculations - James Petterson (Studies in 20th & 21st Century Literature, 2019)
This article explores the relationship between poetry, photography and choreography in the writings of contemporary French poet Dominique Fourcade. Close readings of Fourcade’s 2001 M W alongside other of his works reveal some of the fundamental techniques of his writing, founded on formal recalculations sparked by interaction with other art forms, specifically the photography of Barbara Morgan and Isabelle Waternaux and the dance choreography of George Balanchine, Merce Cunningham, Pina Bausch, Mathilde Monnier and William Forsythe. The analysis also proposes alternative multi-disciplinary directions for the reception of poetry.
Keywords: Dominique Fourcade; Poetry; Elegy; Esthetic Transposition; Poetry and Photography; Poetry and Dance; Poetry and 9/11; Poetry and Prosthesis; Choreography; Stéphane Mallarmé; Merce Cunningham; Pina Bausch; Mathilde Monnier; William Forsythe; Barbara Morgan; Isabelle Waternaux; Jean Epstein; Edouard Manet; Henri Matisse.